The versatile behavior of diamond electrodes — Electrochemical examination of the anti-psychotic drug olanzapine (OL) oxidation as a model organic aqueous solution - Cardozo, Jussara Câmara; da Silva, Djalma Ribeiro; Martínez-Huitle, Carlos A. [UNESP]; Quiroz, Marco Antônio; Vieira dos Santos, Elisama [UNESP] (Elsevier, 2022)
The electrochemical degradation of dilute aqueous solutions of olanzapine (OL), using boron-doped diamond (BDD) anodes as electrocatalysts, was investigated. The studies were carried out in a single-compartment electrochemical cell at three different current densities (10, 30, and 50 mA cm−2), 25 °C, and 50 mg L−1 of OL in 0.05 M Na2SO4 pH (2.0, 4.0 and 6.0) as supporting electrolyte. The OL concentration and feasible by-products of the oxidized solution were monitored during the oxidation process using UV spectrophotometry, chemical oxygen demand (COD), total organic carbon (TOC), and high-performance liquid chromatography-mass spectrometry (HPLC-MS) techniques. Through voltametric studies, it was revealed that OL oxidation involved a direct oxidation stage, characterized by a current peak at +0.8 V (vs Ag/AgCl3M) that behaved as a quasi-reversible process, and an irreversible oxidation stage as well as an indirect oxidation step at +1.65 V (vs Ag/AgCl3M) mediated by physiosorbed ●OH radicals on BDD surface, which were formed by the discharge of water. The dependence of the peak current (ip), as well as the peak potential (Ep), with the potential sweep rate ν (mV s−1), showed that the oxidation depended on the diffusion of OL towards the BDD surface. By using a chronoamperometric analysis, a value of 6.6 × 10−4 cm2 s−1 was estimated for the diffusion coefficient of OL in 0.05 M Na2SO4 pH 2.0, confirming the transport effects. The results of UV and HPLC showed that the OL removal rate increased as the applied current density increased, although the COD and TOC data showed that a better oxidation is achieved at 30 mA cm−2. The results of HPLC-MS were consistent with the removal processes, involving both direct and indirect OL oxidation steps with BDD electrode. In any case, the results clearly confirmed the OL removal from the aqueous solution, achieving 80% of mineralization at applied current densities greater than 30 mA cm−2.
Keywords: Antipsychotic drugs; BDD anodes; Electrooxidation; Olanzapine